Influence of Biochar Based Nano-phosphorus on Phosphorus Uptake and Yield Performance of Groundnut (Arachis hypogaea L.) Grown in Sandy Loam Soils - Kavitha, M.; Prasad, T. N. V. K. V.; Krishna, T. Giridhara; Reddy, G. Prabhakara; Reddy, B. Ravindra; Naidu, M. V. S. (International Journal of Bio-resource and Stress Management, 2025)
An experiment was conducted during 2020 and 2021 at S.V. Agricultural college, Tirupati to improve phosphorus availability by application of biochar-based nano-phosphorus fertilizer in order to improve the phosphorus uptake and groundnut productivity in sustainable manner. Nanoscale phosphorus particles were prepared by the biological method by using Stevia leaf extract as reducing and stabilizing agent. Surface modification of biochar was done through acid wash and gum acacia was used as a binding agent for loading of nano-phosphorous particles and the techniques such as, UV-VIS spectroscopy, Fourier transform infrared spectroscopy (FTIR), Dynamic light scattering (DLS), Transmission electron microscopy (TEM) and X-ray diffraction (XRD) were used to characterize the biochar-based phosphorus fertilizer (BBPF), biochar-based nano-phosphorus fertilizer (BBNPF) and nano phosphorous (NP). The synthesized BBPF, BBNPF and NP mean size was 110.8, 87.6 and 53.7 nm, respectively. The experiments were conducted during two seasons viz., kharif-2020 (June–September) and rabi 2020–21 (November–March) with commercial groundnut variety Dharani. The experiment was laid out in a randomized complete block design contain ten treatments with three replications. The phosphorus content and phosphorus uptake were higher with the soil application of 100% RDP+BBNPF @ 4 kg ha-1. The higher pod yield and haulm yield was recorded with the application of 100% RDP+BBNPF @ 4 kg ha-1. Loading of nano-phosphorus with biochar and the consequent application to the soil enhance the phosphorus availability with an extended period of time.